The diagnostic potential of Asprosin and Meteorin-like proteins in basal and squamous cell carcinomas - Erdogan, Mehmet Mustafa; Erdogan, Esra; Kocaman, Nevin; Yasar, Seyma; Kavak, Songul Yerlikaya (Springer, 2025)
Non-melanoma skin cancer (NMSC) is the most prevalent malignancy worldwide, encompassing primarily BCC and SCC. Differentiating between these two carcinomas and distinguishing them from normal skin tissue can pose diagnostic challenges in certain cases. Adipokines, as regulators of various biological processes, have garnered attention for their potential roles in tumorigenesis. Asprosin (Asp) and Meteorin-like (Metrnl) are newly identified proteins implicated in several diseases, including cancer. Their potential contribution to the pathogenesis of skin cancers such as BCC and SCC remains underexplored. This study aimed to evaluate the expression profiles of Asp and Metrnl in BCC and SCC and to assess their potential utility as diagnostic biomarkers. The expression of Asp and Metrnl proteins was examined by immunohistochemical staining in biopsy samples from 60 control, 60 BCC, and 60 SCC cases obtained from the archive of the Pathology Laboratory of Malatya Turgut Ozal University Training and Research Hospital. Asp immunoreactivity was higher in BCC tissues compared to the other two groups, and it was statistically higher in SCC tissues compared to healthy control tissues. Metrnl immunoreactivity was also higher in BCC tissues compared to the other two groups, and statistically significant in SCC tissues when compared to healthy control tissues. The findings suggest that Asp and Metrnl proteins may serve as valuable biomarkers for distinguishing between BCC and SCC, the two most common non-melanoma skin cancers encountered in routine dermatopathology practice. These adipokines may also provide insights into the underlying pathophysiology of these malignancies, offering potential avenues for diagnostic and therapeutic advancements.
Keywords: Basal cell carcinoma; Squamous cell carcinoma; & Idot;mmunohistochemistry; Asp; Metrnl